Prevalence of impacted and transmigrated canine teeth in a Cypriote orthodontic population in the Northern Cyprus area - Kamiloglu, Beste (BioMed Central, 2014)
BACKGROUND: The aim of this study was two-fold; (1) to evaluate the prevalence and patterns of impacted canines and transmigrated canine teeth, and (2) to evaluate the possible relationships between impacted teeth, malocclusions and systemic conditions in an orthodontic patient population. METHODS: The clinical records and panoramic radiographs of 453 patients [201 (44.3%) male and 252 (55.7%) female] referred to our outpatient clinic between January 2008 and January 2012 were retrospectively evaluated. The number, position, localization (right/left) and transmigration of teeth, as well as sex, age and systemic conditions of patients, were noted. An impacted canine was considered to be transmigrated when at least part of its length had crossed the midline. Complications related to impacted teeth (pain, cystic changes, root resorption or eruption disturbance of adjacent teeth) were also noted. A p-value less than 0.05 was considered statistically significant. RESULTS: Impacted and transmigrated canine teeth were found in 16 (3.53%) and two (0.44%) patients in the study group, respectively. Root resorption was seen in four teeth adjacent to impacted canines. No statistical difference was found among gender, location, malocclusion and impaction of the teeth (p > 0.05). However, maxillary canine impaction occurred significantly more frequently than mandibular canine impaction (p < 0.05). CONCLUSIONS: The early detection of impacted as well as transmigrated teeth is crucial for successful treatment, therefore demographic studies are important. Although larger samples are required, this study provides a baseline regarding the frequency and type of impacted canines in this particular population.